Ein likeverdig skule i framtida? - Peder Haug (Nordisk tidsskrift for pedagogikk og kritikk, 2016)
The article deals with The Ludvigsen committee’s suggestions for future changes in school. The Norwegian Government appointed this committee in 2013 to assess primary and secondary education subjects in terms of the competence society and working life will need in the future. The committee’s recommendations do not specifically refer to the group of students in need of special support and being in danger of marginalization in school. However, some of the proposals could improve school’s function for them. The first part of the article is about what consequences some of the recommendations could have for these students in school. The elements discussed are emphasize on depth learning, increased flexibility in distribution of subjects and teaching hours and a broad perspective on what student competences school should be responsible for. How these changes will function for the students depends upon the implementation. Part two of the article therefore deals with what to consider making the recommendations a chance to succeed. The main points are to build on professional ground, to understand the complexity of the challenges and to make institutions responsible, not only individuals.